Hyperuricaemia: contributions of urate transporter ABCG2 and the fractional renal clearance of urate. Issue 7 (1st December 2015) - Kannangara, Diluk R W; Phipps-Green, Amanda J; Dalbeth, Nicola; Stamp, Lisa K; Williams, Kenneth M; Graham, Garry G; Day, Richard O; Merriman, Tony R
Abstract : Objective: To investigate the contributions towards hyperuricaemia of known risk factors, focusing on fractional (renal) clearance of urate (FCU) and variation in the ATP-binding cassette transporter, sub-family G 2 ( ABCG2 ) gene. Methods: The contributions of age, sex, ancestry, Q141K genotype for ABCG2, FCU, sugar-sweetened beverage and alcohol consumption, metabolic syndrome disorders and measures of renal function to the risk of hyperuricaemia were evaluated by comparing hyperuricaemic (serum urate≥0.42 mmol/L, n=448) with normouricaemic (serum urate<0.42 mmol/L, n=344) participants using stepwise logistic regression. Model performance was evaluated using the area under the receiver operator characteristic curve (AUROC). Results: ABCG2 genotype, FCU, male sex, body mass index, serum triglyceride concentrations, estimated glomerular filtration rate and consumption of alcohol were the best predictors of hyperuricaemia (AUROC 0.90, 81% accuracy). Homozygosity in the 141K variant for ABCG2 conferred an adjusted OR of 10.5 for hyperuricaemia (95% CI 2.4 to 46.2). For each 1% decrease of FCU, the adjusted OR increased by 51% (OR 1.51, 95% CI 1.37 to 1.66). There was no association between ABCG2 genotype and FCU (r=0.02, p=0.83). Conclusions: The ABCG2 141K variant and the FCU contribute strongly but independently to hyperuricaemia. These findings provide further evidence for a significant contribution of ABCG2 to extra-renal (gut) clearance of urate.